Japan-Malaysia Free Trade Agreement:: Expectations and Achievements - Rahman, Khondaker; Molla, Rafiqul; Murad, Md. (Journal of Comparative International Management, 2008)
The Japan-Malaysia free trade agreement (FTA) was signed in 2005 and implemented from 2006 with the expectation that it would further enhance the trade and investment relationship between the two countries. Yet, research suggests that the trade agreement and other tools for expanding trade between partner countries are substantially losing effectiveness. In light of this phenomenon, this study examines the role and effectiveness of the Japan-Malaysia FTA in influencing their bilateral trade. From analyses of time series data for Malaysia’s trade with the world and Japan, in terms of trade volume, trade share, and rate of growth, it is observed that during the first two years of this FTA, its influence on bilateral trade between these two countries was not significant. This research indicates that the agreement is still at a fledgling stage, and has limited scope for influencing and revamping mutual trade. The results provide weak support for the thesis that formation of a free trade agreement or bloc is an effective tool for enhancing trade between partner countries. Although a two years of engagement is not long enough to test any rigorous model nor draw valid conclusions, a FTA is indeed an effective tool as long as partners do not enter into such arrangements with many countries, which may dilute the anticipated outcome of an agreement between two countries.